Peran Viral Marketing, Live Streaming, and e-WOM terhadap Keputusan Pembelian di Live Streaming E-Commerce - Citra Raenalda Kalimantary; Chindy Puspita Dewi; Nazwa Nakiyah Nabila; Putri Fadila; Gracela Marisa Sanapang (Jurnal Online Manajemen ELPEI, 2026)
This study aims to analyze the influence of viral marketing, live streaming, and electronic word of mouth (e-WOM) on purchasing decisions on live streaming-based e-commerce platforms. The study used a quantitative explanatory approach with a survey method of consumers who had made purchases through live streaming commerce. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) to test the measurement model and structural model. The test results showed that all research indicators met the validity and reliability criteria. Empirical findings revealed that viral marketing and e-WOM had a positive and significant influence on purchasing decisions, while live streaming did not have a significant direct influence. Viral marketing acts as an initial trigger that increases consumer awareness and interest through social information dissemination. Meanwhile, e-WOM is the most dominant factor in influencing purchasing decisions because it functions as a form of social validation that can reduce risk perception and increase consumer trust. Live streaming plays a more active role as a means of consumer interaction and engagement that has an indirect impact on purchasing decisions, thus requiring the support of other factors such as trust and credible consumer reviews. In conclusion, an effective digital marketing strategy for live streaming commerce needs to focus on creating viral content and strengthening positive e-WOM, with live streaming being used as a supporting tool to increase engagement and overall marketing effectiveness.